The Impact of Community Generated PPE During the SARS-COV-2 Pandemic in Southeast Alabama and Gulfport Mississippi - Buttars, Benjamin; Fountain, Leigh; Goodwin, Joseph; McLean, Jessica; Olsen, John; Hatton, Trey; Grant, William C.; Vasauskas, Audrey; Hamilton, Caleb; Clemmons, Martin (Frontiers in Health Services, 2021)
Background: The early stages of the SARS-COV-2 pandemic left many hospital systems devoid of personal protective equipment. Community-driven groups manufactured Personal Protective Equipment (PPE) as a form of temporary replacement until supply could increase to frontline healthcare workers. The purpose of this study was to survey hospital systems in Alabama and Mississippi who requested and received PPE to determine recipient opinions concerning community involvement. Methods: A 15-question Qualtrics survey was distributed to hospital systems who requested and received community-generated PPE (CGPPE) from the group known as Alabama Fighting COVID. 275 responses were gathered over a period of 6 months. Results: Survey data showed that most respondents from healthcare and healthcare-associated professions responded that wearing community generated personal protective equipment provided them with the perception of added protection (55.31% of participants selected either “Agree” or “Strongly Agree”), and that it improved their outlook and desire to work during the pandemic (51.77% of participants selected either “Agree” or “Strongly Agree”). Conclusions: Most respondents reported that wearing community generated personal protective equipment not only provided them with the perception of added protection, but that it improved their outlook and desire to work during the pandemic. With these responses in mind, our study raises questions concerning whether local CGPPE distribution could improve well-ness outcomes of healthcare workers (HCWs) not only in relation to decreased viral transmission, but also in favorable psychosocial health assessments. Further implications for research concerning community involvement during future medical crises are indicated, especially with the current rise of the delta variant strain.